1991
DOI: 10.1002/actp.1991.010421013
|View full text |Cite
|
Sign up to set email alerts
|

Semicontinuous emulsion polymerization of vinyl acetate IX. Decomposition of the initiator

Abstract: The way in which the decomposition reaction of a persulfate initiator is influenced by the nature of reactants of the polymerization medium and by the working conditions during the semicontinuous polymerization and copolymerization of vinyl acetate is studied. The rate of the splitting reaction of potassium persulfate is higher in the aqueous phase containing a protective colloid and surfactant. The splitting rate is smaller in the presence of vinyl acetate. The presence of hydrophobic comonomers decreases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The formation of microemulsions is based on the very pronounced decrease of the interfacial tensions between organic and aqueous phases . In the case of a PrOH/H 2 O mixture the air/liquid interfacial tension decreases with increasing alcohol concentration and, above a certain concentration, it is no longer modified by the presence or nature of the surfactant . Therefore in “surfactant-free” systems one can obtain microemulsions only above the high PrOH concentration range (Figures a and a) while in the presence of the surfactant they may be formed over concentration ranges rich in aqueous phase (Figures b and b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The formation of microemulsions is based on the very pronounced decrease of the interfacial tensions between organic and aqueous phases . In the case of a PrOH/H 2 O mixture the air/liquid interfacial tension decreases with increasing alcohol concentration and, above a certain concentration, it is no longer modified by the presence or nature of the surfactant . Therefore in “surfactant-free” systems one can obtain microemulsions only above the high PrOH concentration range (Figures a and a) while in the presence of the surfactant they may be formed over concentration ranges rich in aqueous phase (Figures b and b).…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out on VAc microemulsions have shown that their composition range depends on the nature of the hydrocarbonate moiety of the SCC. , The presence of a more hydrophobic comonomer, for example, 2-ethylhexyl maleate (DEHM), diminishes the probability of microemulsion formation. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The successful incorporation of other highly water‐insoluble monomers via miniemulsion polymerization has been demonstrated 24 . Although the conventional emulsion process of VAE has been studied and even practiced commercially, 25,26 little has been reported on the miniemulsion copolymerization of VAc and gaseous ethylene. Recently, Guo et al 16 reported that gaseous monomer with very low water solubility such as ethylene can be effectively incorporated into a copolymer phase in miniemulsion copolymerization of VAc and ethylene with ethylene partial pressure of 66.7 psig (460 kPa).…”
Section: Introductionmentioning
confidence: 99%